Effects of an automated stride assistance system on walking parameters and muscular glucose metabolism in elderly adults. Issue 11 (28th February 2008) - Shimada, H; Suzuki, T; Kimura, Y; Hirata, T; Sugiura, M; Endo, Y; Yasuhara, K; Shimada, K; Kikuchi, K; Oda, K; Ishii, K; Ishiwata, K
Abstract : Objective: To identify the effects of an automated stride assistance system (SAS) on walking scores and muscle activities in the lower extremities of elderly people. Methods: Seven healthy elderly men (73–81 years) participated in this study. Subjects walked continuously at a constant speed for 50 min on a treadmill with and without the SAS, which is a device to control the walk ratio (step length/cadence) and to add support power to the thigh during walking. A step counter equipped with an infrared device was used to record walking data. The average speeds during treadmill walking were 2.89–3.82 km/h without the SAS and 3.03–4.03 km/h with the SAS. Positron emission tomography (PET) and [18 F]fluorodeoxyglucose (FDG) evaluation of glucose metabolism were conducted on each subject twice after walking with and without the SAS. Results: Walk ratio, walking speed and step length were significantly improved in all subjects by the SAS, while cadence was significantly decreased by the SAS in all subjects except one. The SAS did not have a significant effect on glucose metabolism of the muscles of the lower extremities. There were no significant correlations between change in walking speed and change in glucose metabolism in each muscle without the SAS and with the SAS. In contrast, significant correlations between walking speed and glucose metabolism were shown in gluteus minimus (r = −0.929), hip-related muscles (r = −0.862), soleus (r = −0.907), and medial gastrocnemius (r = −0.952) without the SAS. With the SAS, there were significant correlations in gluteus medius (r = −0.899), hip-related muscles (r = −0.819), and medial gastrocnemius (r = −0.817) in the elderly subjects. Conclusions: The SAS increases walking scores in elderly people without increasing energy consumption of lower-extremity muscles. The elderly subjects with low walking speed showed higher glucose metabolism in hip-related muscles and triceps surae. Thus, this association suggested that decreased walking speed in elderly adults has a higher metabolic cost in these muscle regions.